Stabilization of kaolin clay soil reinforced with single encapsulated 20mm diameter bottom ash column - Muzamir, Hasan; M. S. I., Zaini; N. A. A., Hashim; Wahab, A.; K. A., Masri; Putra Jaya, Ramadhansyah; Hyodo, M.; Winter, M. J.; Sholichin, M.; Haribowo, R. (IOP Science, 2021)
Ground improvement methods are used to reduce the weakness of soft clay, which is low strength and high compressibility. The stone column technique involves replacing any of the soil with crushed stone such as broken rocks or sand which is an efficient method of improving the strength parameters of soil. Bottom ash usage in materials of building will effectively decrease the buildup of the waste and hence protect the environment. This study is to determine the shear strength of kaolin soft clay reinforced with a 20 mm diameter single encapsulated bottom ash column with various lengths. The research will look into the physicomechanical qualities of the materials used, including subsoil and bottom ash. Three (3) batches of samples with each batch consists of five (5) samples were prepared by using compaction method. All kaolin samples with a diameter of 50mm and height of 100mm with single encapsulated bottom ash columns with various lengths which are 60mm, 80mm, and 100mm were tested under Unconfined Compression Test (UCT). The result illustrated that the strength of samples increases as the height and volume of encapsulated bottom ash column increases.